Short communication: Effects of the various source areas of Indonesian bay leaves (Syzygium polyanthum) on chemical content and antidiabetic activity - Indah Dewijanti; WIBOWO MANGUNWARDOYO; ASTARI DWIRANTI; MUHAMMAD HANAFI; NINA ARTANTI (Society for Indonesian Biodiversity, 2020)
Abstract. Dewijanti ID, Mangunwardoyo W, Dwiranti A, Hanafi M, Artanti N. 2020. Short communication: Effects of the various source areas of Indonesian bay leaves (Syzygium polyanthum) on chemical content and antidiabetic activity. Biodiversitas 21: 1190-1195. Bay leaves (Syzygium polyanthum (Wight) Walp) are from an Indonesian plant species belonging to the Myrtaceae family. The Indonesian name for this plant is salam; it is found in Sumatra, Kalimantan, and the Java Islands. Its leaves are the part of the plant commonly used. Salam leaves are usually consumed by people as a food flavoring, but are also used as a traditional antidiabetic medicine. The purpose of this study was to discover the effects of salam leaves’ origins on their chemical content and antidiabetic activity. For this reason, salam leaf samples were collected from three different provinces in Java (West Java, Central Java, and East Java). The samples were extracted by boiling in water. Phytochemical screening, chemical analysis using TLC, HPLC, LC-MSMS, and FTIR, and antidiabetic in vitro testing using alpha-glucosidase inhibition methods were conducted on the salam leaves’ water extracts. The results showed that salam leaf extracts from all three provinces contained quercetin. However, the salam originating from East Java also contained coniferin, the salam from Central Java contained juncusol, and the salam from West Java contained retucine. The salam leaves originating from East Java showed the lowest antidiabetic activity, whereas salam leaf extract showed significantly higher antidiabetic activity. As conclusion, a plant’s growth origin affects its chemical content and antidiabetic activity.